Improving Mechanical Properties of Bioplastics from Sweet Potato Peel Waste with CMC and Gum Arabic - Deny Aditya Pratama; Dwi Saputri; Sani Sani; Lilik Suprianti (Jurnal Kartika Kimia, 2026)
Plastic waste continues to be an environmental issue in Indonesia, where the country ranks as the second-largest producer of plastic waste in the world. Bioplastics, derived from renewable materials such as starch, have the potential to serve as an alternative to conventional plastics. The objective of this research is to formulate biodegradable bioplastics utilizing sweet potato peel starch, carboxymethyl cellulose (CMC), and gum Arabic, with glycerol added as a plasticizer. Initially, extraction was performed to obtain starch from sweet potato peels. Subsequently, the bioplastic production process was carried out using the wet mixing followed by the casting method by mixing 5 grams of sweet potato starch with the CMC in various weights (0.1, 0.2, 0.3, 0.4, and 0.5 grams) and gum Arabic (1, 1.5, 2, 2.5, and 3 grams). Mechanical property tests were conducted to evaluate the quality of the bioplastics, including tensile strength, elongation, and apparent modulus. The results indicate that higher concentrations of CMC and gum Arabic enhance tensile strength and rigidity, with a maximum tensile strength of 1.51 MPa achieved. However, increasing CMC concentration can reduce elongation properties. The bioplastics exhibited water absorption ranging from 15.3% to 81.3%, while biodegradability tests demonstrated that samples reached degradation levels of up to 93.8% within 28 days. This study demonstrates that sweet potato peel starch, combined with CMC and gum Arabic, can produce bioplastics with favorable mechanical properties and environmental friendliness, thus presenting a potential alternative method for reducing plastic pollution in Indonesia.